Thurgood Marshall : a life in American history - Crew, Spencer R., 1949- (Black history lives., 2019)
"This compelling new biography introduces the reader the constant battles for equality faced by African Americans through a study of the career of Thurgood Marshall, who believed in the power of the law to change a society."